Treatment failure in case of typhoid fever imported from India to Czech Republic, December 2008--January 2009 - Hozáková, Lubomíra; Orságová, Irena; Zjevíková, Alena; Chmelařová, Eva (Euro surveillance, 2009)
In this report we describe a case of typhoid fever in a Czech patient with history of travel to India and discuss antibiotic treatment failure which led to the relapse of fever.
Keywords: dospělí; Adult; India; Typhoid Fever; lidé; Travel; Salmonella typhi; Treatment Failure; cestování; hospitalizace; antimalarika; Male; Czech Republic; Hospitalization; neúspěšná terapie; Česká republika; mužské pohlaví; Indie; Antimalarials; břišní tyfus; Humans